2017
DOI: 10.17261/pressacademia.2017.501
|View full text |Cite
|
Sign up to set email alerts
|

Role of knowledge management in achieving organizational performance: Proposed framework through literature survey

Abstract: Purpose-Keeping in view the increasing demand of knowledge management, Researchers has recognized the need for structures for appraising the influence of knowledge management (KM) on organizational performance (OP). Despite of the wide performances of KM, at present there is no uniform structure for evaluating the OP. The basic intent of this study / research is to plan the appropriate methodologies to evaluate the impact of KM to enhance OP. Methodology-At the end of this paper, the author proposes a theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…Based on the empirical findings, hypothesis H1 reveals that a greater acceptance level of knowledge management in banking likely leads to greater financial effectiveness in banking. These results are consistent with prior studies undertaken by Dröge et al (2003), Chen and Huang (2007), Jamil (2017), Imran (2014), Ngahu and Mbugua (2017) and Ahmed et al (2015). In line with the hypothesis H2, the empirical results indicate that three elements (FOR, COP & CNT) of corporate structure have a statistically positive effect on the acceptance of knowledge management in business.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Based on the empirical findings, hypothesis H1 reveals that a greater acceptance level of knowledge management in banking likely leads to greater financial effectiveness in banking. These results are consistent with prior studies undertaken by Dröge et al (2003), Chen and Huang (2007), Jamil (2017), Imran (2014), Ngahu and Mbugua (2017) and Ahmed et al (2015). In line with the hypothesis H2, the empirical results indicate that three elements (FOR, COP & CNT) of corporate structure have a statistically positive effect on the acceptance of knowledge management in business.…”
Section: Discussionsupporting
confidence: 93%
“…Second, the management of knowledge could directly enhance organizational performance. Therefore, the management of knowledge is regarded as a crucial element in creating competitive advantages and augmenting organizational performance (Chen & Huang, 2007;Jamil, 2017). Additionally, Salojärvi, Furu, and Sveiby (2005) confirmed that the management of knowledge is associated with organizational growth, whereas Hsu, Lawson, and Liang (2007) affirmed the magnitude of accepting that the management of knowledge is correlative to organizational performance.…”
Section: Theoretic Frameworkmentioning
confidence: 94%
“…Relevantly, a meaningful relationship between customer KM and marketing competencies was reported by Fan and Ku [46] who found that KM can also significantly empower firms in their strategic decision-making. Moreover, as indicated in some other past studies [33,47,48], firms with successful KM can effectively form positive and superior customer relationships, and such relationships affect marketing performance in a positive manner.…”
Section: Relationship Between Crm Knowledge Management and Marketing ...mentioning
confidence: 69%